ANALYZING THE EFFICIENCY AND IMPACT OF PUBLIC EXPENDITURE ON ECONOMIC PRODUCTIVITY IN IRAQ: A STUDY FOR THE PERIOD (2010-2020) (World Economics and Finance Bulletin, 2024)
This research deals with the performance of public expenditure and its productivity in Iraq during the period (2010 – 2020). It highlights the importance of stable financial policies and flexible strategies to improve the economic performance of public expenditure in Iraq. The analysis reveals ineffective use of public expenditure, as data shows significant fluctuations in spending, and the increase in public expenditure was not accompanied by an increase in its partial and total productivity. The main problem lies in the governments' inability to effectively utilize public expenditure to enhance productivity. The research hypothesizes that there is a negative relationship between increased spending and decreased productivity. The research concludes that poor management and planning are the primary barriers to productivity decline, while recommendations include increasing transparency, redirecting expenditure to key sectors, and improving the efficiency of public expenditure.